Interferon γ-release assays for detecting latent tuberculosis infection in patients scheduled for anti-TNFα therapy. Issue 1 (20th November 2010) - Greveson, Kay; Murray, Charlie; Toumpanakis, Christos; Epstein, Owen; Hamilton, Mark; Lipman, Marc
Abstract : Screening for, and treatment of, latent tuberculosis infection (LTBI) before anti- tumour necrosis factor α therapy has been shown to decrease the incidence of active tuberculosis by more than 80% and is recommended before initiation of treatment. In the absence of a 'gold standard' test for LTBI, current screening involves taking a clinical history of risk factors, chest radiograph and tuberculin skin test. Alternative cellular immune-based screening tests have been developed to detect Mycobacterium tuberculosis infection. This paper summarises the current position and advances in the use of newer screening strategies for LTBI.